Implementation of Psychology of Sexual Abuse Cases in Legal Criminology Handled by Investigators of Bintuni Bay Police Crimes - Muhammad Irdyan Soewatijo; Mohammad Saleh (Dinasti Research, 2024)
Psychological impact on victims of sexual abuse is very disruptive to development and future life due to prolonged trauma so that victims will be inferior and afraid to socialize with the community, so the role of the Police in tackling and eradicating the crime of sexual abuse must be truly firm and professional so that there is a deterrent effect for the perpetrator. The problem in this study is how the implementation of psychology towards victims of sexual abuse cases according to legal criminology, how do investigators of the Bintuni Bay Police Criminal Investigation Unit handle sexual abuse cases until the submission of files to the Court (from investigation to submission of files to the Court), what are the obstacles in the investigation of sexual abuse cases in terms of psychology towards victims of sexual abuse cases according to legal criminology. The result of this research is: Sexual abuse committed against minors will certainly have an impact on the psychological and other development of the child. The psychological impact on children will give birth to prolonged trauma which can then give birth to unhealthy attitudes, such as inferiority, excessive fear, disturbed mental development, and ultimately result in mental retardation. This situation is likely to become a bad memory for the child victim of sexual abuse. The implementation of investigations carried out by investigators against suspected perpetrators of criminal acts related to sexual abuse are as follows Conducting examinations of victims of criminal acts related to sexual abuse, Examining witnesses to hear their testimony, Making Minutes of Investigation, Searching, Confiscation of evidence used to commit criminal acts, Submission of case files to the court for trial If in the process of examining criminal acts related to sexual abuse has been completed, the file will be submitted to the court.Obstacles related to the human resources of investigators, the victim is still a child, there are no witnesses who saw directly and witnesses do not want to come to handle the investigation of criminal acts of intercourse and sexual abuse of children committed by investigating officers. Overcoming obstacles related to the human resources aspect of the investigator tries to optimize the existing investigators, in addition to proposing additional investigators. The absence of witnesses who saw this directly was overcome by increasing the number of witnesses who would provide information about cases of sexual intercourse against children, while for witnesses who did not want to come to provide information to investigators, a re-call would be made. If they still do not want to come, then they will be visited at home so they can provide information. The suspect did not confess to being a very serious obstacle for investigators. To reveal this case, investigators conducted a case title at the location, processed evidence and presented more witnesses.